Together We Can Change the Issues of Polluted Air: Identity as A Jakarta Citizen Could Predict Collective Action through Group Efficacy - Alfiannor, Muhammad; Djuwita, Ratna (Future Science, 2024)
In high-density metropolitan areas, urban air pollution increasingly affects the physical environment of cities. The city of Jakarta has poor air quality which can threaten the health of its citizens. The purpose of this research was to find out whether the role of fusion identity with the city of Jakarta in the collective action demanding clean air in Jakarta is mediated by group efficacy and group-based anger. a correlational survey approach with cross-sectional was used for data collection. People who live in Jakarta, Bogor, Depok, Tangerang and Bekasi are the samples of this study. After data collection, 127 people were found with an age range of 17-47 years. Based on the results of the research, it proves that in this study there is a role for fusion identity towards collective action demanding clean air in mediation in Jakarta by group efficacy which can be confirmed. This finding is different from SIMCA, which shows that group-based anger emotions can mediate the indirect effect of social identity on collective action. In this study, we found that identity fusion has no effect on collective action.